Pengaruh Komunikasi Tatap Muka Terhadap Kesadaran Swadaya Masyarakat : Studi tentang Pengaruh Komunikasi Tatap Muka Tim Pengelola PNPM Mandiri Pedesaan terhadap Kesadaran Swadaya Masyarakat dalam Pembangunan Sarana dan Prasarana di Dusun Kebon Kerep, Desa Darmareja, Kecamatan Nagrak, Kabupaten Sukabumi - Maielayuskha; Siti Nuryani (Jurnalika : Jurnal Ilmu Komunikasi, 2022)
This study aims to determine the implementation of face-to-face communication carried out by the Rural PNPM Mandiri Activity Management Team, awareness of community self-help in the development of facilities and infrastructure, as well as to describe the effect of face-to-face communication by the Rural PNPM Mandiri activity management team on the awareness of community self-help in the development of facilities and infrastructure in rural areas. Dusun Kebon Kerep, Desa Darmareja, Kecamatan Nagrak, Kabupaten Sukabumi. This study uses the associative analysis method with a rating scale measurement and analysis using a continuum line. Meanwhile, to find the relationship between variables, the Pearson product moment correlation formula and the coefficient of determination formula are used. To find out the truth test of the correlation calculation, hypothesis testing is carried out using the t-test formula. The research sample was 148 people from a total population of 2,790 people with a disproportionate stratified random sampling technique. While the object of research is the community of Desa Darmareja which consists of village officials, PNPM actors, and the local community. The results of the study showed that TPK's face-to-face communication was in a fairly good category, with an average score of 3.1. Meanwhile, the awareness of community self-help in the development of facilities and infrastructure is categorized as quite good, with an average score of 3.2. There is an effect of face-to-face communication between the management team of PNPM Mandiri Rural activities on the awareness of community self-help in the development of facilities and infrastructure with a correlation value of 0.5343 (r count) greater than 0.159 (r table). The contribution of the influence of face-to-face communication on the awareness of self-help of the community is obtained by 28.55% while the remaining 71.45% is the influence of other factors. For hypothesis testing with the t-test formula with the calculation results of 9.036, the X variable has a significant effect on the Y variable because 9.036 (t count) is greater than 1.771 (t table), so there is a positive and significant effect of face-to-face communication on self-help awareness of the community. in the construction of facilities and infrastructure in Dusun Kebon Kerep, Desa Darmareja, Kecamatan Nagrak, Kabupaten Sukabumi.